Development of Bamboo Composites for Wind Turbine Blade Applications - Pratama, Moh Romandika; Suwandi, Agri; Adriant, Ziani; Förster, Ralf; Zaratin, Dede Lia (Proceedings of the International Conference on Green Technology; Vol 13 No 1 (2023): Proceeding of International Conference on Green Technology, 2024)
Wind turbine is one of the electricity generation devices that utilizes wind energy as the driving force, typically through its wind turbine blades. Currently wind turbine blades often use composite materials made from synthetic materials, which can be relatively expensive. The objective of this research is to transform synthetic composite materials into natural fiber composites that are relatively inexpensive and environmentally friendly. This is achieved by conducting testing on black bamboo fiber composites to determine their strength values using different resin ratios. This testing utilizes tensile testing with ASTM D3039 and ASTM D638 standards. The manufacturing of wind turbine blades is carried out by creating a mold, followed by forming them according to the SG6042 standard. Subsequently, a coating process is applied to ensure the evenness of the blade's surface using epoxy resin. The tensile testing results show that the highest tensile strength was achieved with the 3:9 ratio, both using ASTM D3039 and ASTM D638 standards. The tensile strength values were 7.50 MPa with a 3.2% increase for ASTM D3039 and 10.76 MPa with a 4.92% increase for ASTM D638. This research shows that wind turbine blades can be made from bamboo fiber composite.